2014
DOI: 10.1080/01691864.2014.894940
|View full text |Cite
|
Sign up to set email alerts
|

Improved passivity criterion in haptic rendering: influence of Coulomb and viscous friction

Abstract: In this paper, a new criterion for passivity of haptic devices is obtained. This criterion creates a relationship between Coulomb friction coefficient, viscous friction coefficient, sampling rate, and the maximum simulated stiffness. The process of derivation of the passivity criterion is described in detail. This criterion is improved compared with other existing criteria and predicts passivity in haptic rendering more accurately. In particular, for speeds of less than 5 cm/s, the new passivity criterion shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Another paper from Mashayekhi et al 42 is included as it is quite different from their previous work. 46 This paper identify the need to extend the stability criterion developed in a previous paper 45 to work for both small and large values for damping as well as time delay. While the increased range of these two parameters are thoroughly studied in this paper, the authors also claim that any other dynamic effect can be accommodated in the framework as long as it is linear.…”
Section: Instability Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Another paper from Mashayekhi et al 42 is included as it is quite different from their previous work. 46 This paper identify the need to extend the stability criterion developed in a previous paper 45 to work for both small and large values for damping as well as time delay. While the increased range of these two parameters are thoroughly studied in this paper, the authors also claim that any other dynamic effect can be accommodated in the framework as long as it is linear.…”
Section: Instability Factorsmentioning
confidence: 96%
“…Mashayekhi et al 46 conduct a study to improve the passivity criterion proposed previously by Diolaiti et al 47 They use analytical and numerical methods to prove that the new criterion is more accurate with lowspeed cases while they consider experiment as future work.…”
Section: Instability Factorsmentioning
confidence: 99%
“…In references such as 13,14 and later improved in 15 it is shown that minimum dissipated energy due to Coulomb friction is more than the maximum generated energy due to quantization and sampling, in most of the famous haptic devices. Thus these nonlinear phenomena can be removed by each other, leading to Figure 3, as used in many references such as.…”
Section: System Descriptionmentioning
confidence: 99%
“…Although an actual haptics controller contains several non-linear phenomena like Coulomb friction, quantization, human operator dynamics, actuator saturation, and unilateral constraint, the same are avoided here. The reason being: quantization induced energy can be dissipated by Coulomb friction [13,14]; and, in most cases human operator adds stability to a haptic device by reinforcement of his own damping [7,8].…”
Section: Dual-rate Haptics Controllermentioning
confidence: 99%